Efeito agudo no afeto e divertimento de idosos praticantes de treinamento multicomponente, treinamento de força e caminhada - Souza, Leonardo Fernandes de (2024)
Physical exercise for older adults, such as strength training (ST), multicomponent training (MCT), and walking (CAM), plays an essential role in physical and emotional well-being. In addition to the physical benefits, these practices also contribute to the development of affection and enjoyment, creating a social and relaxed environment that improves mood, promotes interpersonal connections, and increases quality of life. The present study aimed to evaluate the acute effect of MCT, ST, and CAM on affection and enjoyment in older adults. The study is justified by the need to obtain more information about the effects of MCT, ST, and CAM in relation to affection and enjoyment in older adults, since this information is extremely important for adherence to training programs. The project consisted of older women aged 60 to 75 years. Fifteen women familiar with MCT, ST, and CAM, who had at least 3 months of practice, participated in the study. The Feeling Scale, the Felt Arousal Scale, the Enjoyment Scale (PACES) and the Exercise Intensity Preference and Tolerance Scale (PRETIE-Q) were used before, during and after the walking, strength training and multicomponent training sessions, with a one-week interval between each session. Statistical analyses were performed using the SPSS 20.0 statistical software package. The findings indicate that different types of training influence enjoyment in different ways, which is crucial for planning exercise programs aimed at long-term adherence. These findings suggest that the choice of training type can be directed according to the practitioner's emotional and pleasure goals, contributing to greater adherence and satisfaction with physical exercise.